Characterizing the emission behaviors of cumulative VOCs from automotive solvent-based paint sludge. (1st September 2022) - Liu, Zewei; Huang, Zechun; Yan, Yusen; Liu, Tingting; Lv, Tianfeng; Chen, Yu; Yang, Jinzhong; Die, Qingqi; Zhao, Youcai; Huang, Qifei
Abstract: Volatile organic compounds (VOCs) diffused from paint sludge are potential hazard contributing significantly to environmental pollution and exposure to them can cause severe health issues. In this paper, a diffusion-controlled model was firstly developed for characterizing the emission behaviors of cumulative VOCs from automotive solvent-based paint sludge based on the worst field management scenario. The presented model is characterized by two key parameters: the diffusion coefficient ( D m ) and the initial emittable concentration ( C m, 0 ), which can be simultaneously obtained by our proposed ER-history method. Four major components were detected including 1-butanol, butyl acetate and 1, 2, 4-trimethylbenzene and 1-ethyl-4-methylbenzene. In addition, the model was validated by using environmental data in a ventilated test chamber, proving that the model is reliable and convincing. However, relative deviations of 1-butanol and butyl acetate are larger than those of 1, 2, 4-trimethylbenzene and 1-ethyl-4-methylbenzene, indicating that the model is more accurate for predicting hydrophobic VOCs release than those of hydrophilic VOCs. Besides, an increase in C m, 0 and D m tends to enhance VOCs cumulation release. Our studies provide new insight into experimental designs for rapid model parameters measurement and a sound basis for estimating VOCs cumulative release from paint sludge as well as for hazardous waste. Graphical abstract: Image 1 Highlights: The emission behavior of cumulative VOCs from paint sludge was characterized. The model was validated by comparing the prediction value with experimental data. The estimations of oxygenated compounds are less accurate than those of aromatic hydrocarbons. D m will have little influence on VOCs cumulation release at the late stage.